COURTYARD OF THE HOUSING AREA IN THE EYES OF THREE GENERATIONS OF ITS INHABITANTS (City: History, Culture, Society, 2020)
This article examines changeability/non-changeability of the notions of the common communicative area at the example of one courtyard in the housing area of Odesa. Since "present city life includes numerous and various cultural features, styles of life and forms of owning of city space" (Holston, Appadurai, 1996), and anthropology gives a possibility to explore how exactly "global processes reflect on the particular person's life and the whole communities on the macrolevel" (Prato, Pardo, 2013), it seemed possible for us to choose as an exploration object one "courtyard", meaning the space in between of multi-story houses. XX century's second half known as the time of global urbanization, as a result of which at the beginning of the XXI century most of humanity turns out in the cities. Soviet modernization, including urbanization, was a part of those processes. USSR's dissipation and Ukraine's formation led to the change of many of every day's practics. All those processes influenced human societies and various local communities. We tried to find out how courtyard's inhabitants under all those complex processes changed their view on the notion of common space. Chronologically this research covers the period since first settlers in the new houses (1979–1980 yy.) until today (the research was set in the spring of 2018 y.).Were used methods of profound themed interview and mental mapping, with the help of which are explored views of three age groups of surrounding houses at common space between them. That way lets to embrace inhabitant's understanding of the courtyard as the common space for the examined period.The main research strategy is started by structuralists method of binary oppositions. For the analysis of changeability/non-changeability of the notions about the courtyard's common space were used binary oppositions collective/individual, activity/indifference, owned/foreign.Noticed by us tendencies of development of the notions about the courtyard's common space directed from collectiveness to individualism, from activity to indifference, from commonality and "our" space to the obscurity of foreign and incomprehension of owning the space."
Keywords: anthropology, city, sleeping area, Odessa, representation, common space, mental mapping, yard, binary oppositions